Spiritualitas Sunder Warumbe Dalam Puisi “Nyanyian Angsa” Karya W.S Rendra - Kristiawan, Purnomo (KENOSIS: Jurnal Kajian Teologi, 2023)
Prostitution or prostitution is one type of work that has existed for the rest of human history. Joshua 2:1, 6:17-25 tells us that a prostitute named Rahab was used by God to hide Israel's scouts from the Canaanites. In Luke 7:36-50 it is said that the Lord Jesus forgave a sinful woman (prostitute) who oiled His feet. This article seeks to examine the issue of prostitution is actually a structural problem related to economic, educational, justice, political and other issues. In the poem, The Song of the Swan, the responses of the Pimps, Doctors, and Priests to the Olive Mary are countered by the response of the "Bride" to Mary Olive. This paper uses a qualitative research method that utilizes a literature study of the main literature on the poem Goose Song by W.S. Rendra to find the pattern of the spirituality of Sunder Warumbe. In this paper it is found that the journey of Mary the Olives is a spiritual journey of mystical encounter with the Lord Jesus, going through stages: Slumped and rejected in the hustle and bustle of the world, pulling over from fanfare, cleansing oneself, self-examination, and the mystical experience of encounter with the Lord Jesus lived through copulation.